Genetic variants and characterization of MODY in a single, large pediatric referral center - Lily Deng; Amy S. Shah; Mansa Krishnamurthy (Journal of Clinical & Translational Endocrinology)
Background: Identifying Maturity-onset diabetes of the young (MODY) is essential as treatment differs from other forms of diabetes. Clinical characteristics and MODY probability calculator (MPC) scores were evaluated in patients with MODY. Methods: Retrospective chart review using MODY diagnoses and genetic testing was performed to identify patients with MODY gene variants at a large, pediatric tertiary referral center. Demographics, islet autoantibodies, and co-morbidities were evaluated with treatment change after diagnosis of MODY. Probability scores were calculated using the MPC. Results: Thirty-nine patients were identified with MODY. MODY comprised 1 % of the population with diabetes. Mean age and HbA1c at diagnosis were 12.2 years and 7.9 %, respectively. Positive islet cell autoantibodies were seen in 2 individuals. For race, 23.1 % self-identified as Hispanic, Black, or Asian/Pacific Islander. Interestingly, 39.47 % did not require medication at diagnosis while 44.74 %, 10.53 %, and 2.63 % were treated with insulin, Metformin, and GLP-1 RA respectively. Seventy-four percent of patients with MODY had MPC scores of > 75 %. Targeted treatment with sulfonylureas was used for 38 % of total patients who remained on medication, and 20.5 % of patients were able to discontinue medication. Average HbA1c decreased for all patients with MODY regardless of medication treatment type at follow up. Conclusions: Our data reveals that the presence of positive islet cell antibodies may not preclude a diagnosis of MODY if there is a strong clinical suspicion. High MPC scores correlated with diagnoses of MODY except in patients with insulin dependence. Diagnosis of MODY led to targeted treatment changes.